Las fuentes eclesiásticas para la historia social de México - Connaughton Hanley, Brian Francis; Connaughton, Brian F. (Univ. Autónoma Metropolitana, 1996)
"Thoughtful collection of essays on the rich research material for social history available in ecclesiastical archives. Twenty-two historians study diocesan juzgado (ecclesiastical court) records, parochial archives, reports of diocesan visits, religious pamphlets, and similar sources, aptly mixing source analysis and examples from their own investigations. Based on recognition that church records, because of their inclusive nature, are essential for understanding key features of Mexican social and political history. Commendable effort"--Handbook of Latin American Studies, v. 58